Import Substitution in Regional Industrial Production: Theoretical and Practical Aspects - Animitsa, Yevgeniy Georgievich; Animitsa, Polina Yevgenyevna; Glumov, Anton Anatolyevich (Economy of Regions, 2015)
The article proves the important role of import substitution in the economic security protection of state and its regions, especially in times of crisis, geopolitical and economical instability. The authors argue that the problem of import substitution is not modern, trendy scientific stream. The issue of displacement of import goods by domestic ones was brought up in famous classic theories of mercantilists. The particular emphasis is placed on the analysis and systematization of different scientific approaches, which are utilized by native and foreign scientists to bring out the matter of “import substitution" to determine its essential characteristics. The authors suggest their own interpretation of the import substitution notion. In the article, the most significant pro and contra arguments in import substitution policy are defined. The regional aspects in the import substitution are approved: case study - organization of industrial import substitution in the Sverdlovsk region. In the article, the authors analyze the subject matter of the Program “Development of Intraregional Industrial Cooperation and Implementation of an Import Substitution in Branches of Industry in the Sverdlovsk Region.'' It is resumed, that active policy of import substitution in the industry may become the driver of regional economic development.